Human aspects of information security in organisations. (February 2016) - Safa, Nader Sohrabi; Solms, Rossouw von; Futcher, Lynn
Abstract : Information is core to the well-being of any modern-day organisation. In order to satisfactorily protect this important asset, human, organisational and technological aspects play a core integrative role in information security. Both technological and organisational control aspects are critically important, but both of these are closely related to people. Information security technology cannot guarantee the safety of information assets in organisations. A range of human aspects also need to be taken into consideration. Nader Sohrabi Safa, Rossouw von Solms and Lynn Futcher of the Nelson Mandela Metropolitan University, South Africa show that, while people are often the weakest link, through cooperation and coordination they can also be a source of great strength in developing effective and efficient defences.